A Framework of Business Process Re-engineering Factors and Organizational Performance of Nigerian Banks - Ringim, Kabiru Jinjiri; Razalli, Mohd Rizal; Hasnan, Norlena (Canadian Center of Science and Education, 2012)
The aims of this paper is to present a framework on the data collected regarding our research study on Effect of BPR factor on organization performance with moderating role of Information technology. A survey method was used to administer 560 questionnaires to Nigerian banks (Commercial, Microfinance and Primary mortgage finance). Data screening and cleaning was conducted to enable satisfy the assumptions of multivariate analysis. Therefore, the assessment of the missing data, outliers, normality, linearity, and multicollinearity were performed. In addition, factor analysis (PCA) was conducted with help of Statistical Package for Social Science (SPSS). The results were found to meet the requirement for multivariate analysis